SCHOOL ADMINISTRATION TRANSFORMATION: IMPROVING THE PERFORMANCE OF PRINCIPALS, ADMINISTRATORS, AND SCIENCE TEACHERS WITH A MANAGEMENT INFORMATION SYSTEM (SIMA) MODEL - Nasution, Satri Dwi Kurnia; Karnati, Neti; Rugaiyah, Rugaiyah (LPPM Universitas Jambi, 2025)
This study aims to develop and evaluate a digital-based archive management model for a quality assurance system in elementary schools, addressing the inefficiency of traditional archiving practices and the absence of digital archive management. The research employs a Research and Development (R&D) approach using the Successive Approximation Model (SAM) and a mixed-methods strategy. The population consists of science teachers in Bekasi Regency, with data collection conducted through pre-tests and post-tests. The SIMA application was validated by three experts, followed by small-group trials with 40 teachers and large-group trials with 750 respondents. The effectiveness of the SIMA application was tested using significance testing with a paired-sample t-test. The results reveal that (1) expert validation categorized the digital-based archive management application as